2.9 Å Resolution Cryo-EM 3-D Reconstruction of Close-packed Virus Particles - Liu, Zheng (Structure, 2016)
Single particle cryo-EM typically discards close-packed particle images as unusable data. Here, we report an image processing strategy and case study of obtaining near-atomic resolution 3-D reconstructions from close-packed particles. Multiple independent de novo initial models were constructed to determine and cross-validate the particle parameters. The particles with consistent views were further refined including not only Euler angles and center positions but also defocus, astigmatism, beam tilt, overall and anisotropic magnification. We demonstrated this strategy with a 2.9 Å resolution reconstruction of a 1.67 MDa virus-like particle of a circovirus, PCV2, recorded on 86 photographic films. The map resolution was further validated with phase randomization test, local resolution assessment, and the atomic model was validated with MolProbility and EMRinger. Close-packed virus particles were thus shown here not only useful for high-resolution 3-D reconstructions but also allow data collection at significantly improved throughput for near-atomic resolution reconstructions.